ENERGY EFFICIENCY OF BUILDINGS TODAY - Šmate, Līga; Cūkmačs, Arturs; Pleikšnis, Staņislavs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2023)
Nowadays, we hear the words energy efficiency and zero energy building more and more often. The concept of zero-energy building and energy-efficient building is becoming the goal of building design. Sustainable construction, which includes proper methods, materials, technologies, can ensure environmentally friendly use of natural resources and mitigation of global warming. Construction is an industry that does not stand still and almost all the time we see the construction of new buildings, the renovation of existing buildings, etc., but do these buildings meet modern standards? The authors will perform the necessary calculations to find out to what extent a real construction object meets modern requirements and how the energy efficiency of this object could be further improved.